Upaya Pengelolaan Konka Hipertrofi dengan Pendekatan Pelayanan Kedokteran Keluarga - Muhammad Arvin Harwansya; Noviana Zara (Jurnal Medika Nusantara, 2024)
The patient came to the Tanah Pasir Health Center public poly with nasal complaints blockage that is aggravated in 1 month. This complaint of nasal congestion is felt until the patient has difficulty breathing. Nasal congestion does not improve after changes position. Headaches are felt occasionally. Fever (-), bad nose (-), and runny nose (-). The calculation of the body mass index was obtained 22.89 kg/m2 (normal). Primary data was obtained through anamnesis and physical examination at the Tanah Pasir Health Center and home visits. The assessment is carried out based on the initial holistic diagnosis, process, and end of the visit. The interventions carried out include education on the importance of avoiding triggering factors from complaints, taking medication and controlling regularly. Patients are also educated about diet and education about receiving treatment at health service facilities such as health centers and hospitals.